A review on the sustainability of smart buildings that combine green and photovoltaic rooftops in cold climate regions - Ali, Dalia Mohammed Talat Ebrahim (International Conference “Environmental Engineering”, 2023)
A rooftop of a building could be ultimately utilized to retrofit the implementation of smart and sustainable solutions. Green roof systems play a significant role in terms of reducing heat loss and energy consumption, making them a sustainable solution for countries with cold climates. Additionally, rooftops are a convenient space to install photovoltaic (PV) panels to produce solar energy. According to one German study, the energy produced from solar panels is 7% higher when panels are placed on a green substrate in comparison to when they are placed on hard standings. The combination of both PV and green rooftops in countries with cold climates requires a particular selection of plants and roof design solutions. There are far more studies that cover PV-green roofs in countries with warm or moderate climates. However, not as many for countries with cold climates. This paper sheds light on this area of study to assess the practicability of the integration of PV-green rooftops in cold regions, by reviewing case studies of the benefits and analysis of rooftops utilized by combining PV and green roofs, integrating both solutions to the building’s smart energy system, and reusing grey water to maintain the greenery of the rooftop, to attain a sustainable system. The experimental case studies presented in this paper, which are done by different researchers, show that PV-Green rooftops are an advantageous hybrid solution to implement even in countries with harsh winter conditions, and are more sustainable than stand-alone PV panels.
Keywords: photovoltaic panels; green roofs; sustainable; smart buildings; energy